2001
DOI: 10.1095/biolreprod65.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Morphological Traits of Oocytes Retrieved from Aging Mice after Exogenous Ovarian Stimulation1

Abstract: The present study aims to shed light on the origin of abnormal oocytes ovulated by aged females. In order to reach this goal, cellular and morphological traits of ovulated oocytes from hybrid (C57Bl/6JIco female x CBA/JIco male) female mice retrieved after exogenous ovarian stimulation at the age of 12, 40-42, 50-52, or 57-62 wk were analyzed. Aging of female mice was associated with 1) decreased number of ovulated oocytes; 2) increased percentage of cumulus-free oocytes; 3) raised percentage of oocytes with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 11 publications
7
62
1
1
Order By: Relevance
“…This study revealed that adult mouse ovarian response to gonadotropin stimulation declines with increasing reproductive age as shown by the decrease in the number of oocytes collected (Table 1). Our observation support the findings of a previous study showing that the number of oocytes retrieved declined with increased mouse maternal age [24]. The mechanism of poor ovarian response to gonadotropin stimulation is not clear at the present time.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study revealed that adult mouse ovarian response to gonadotropin stimulation declines with increasing reproductive age as shown by the decrease in the number of oocytes collected (Table 1). Our observation support the findings of a previous study showing that the number of oocytes retrieved declined with increased mouse maternal age [24]. The mechanism of poor ovarian response to gonadotropin stimulation is not clear at the present time.…”
Section: Discussionsupporting
confidence: 86%
“…Ultrastructural abnormalities have been found in correlation with increase in maternal reproductive age of mouse oocytes [24]. Results of the present study demonstrated for the first time that cryo-survival of oocytes is related to maternal age, revealing that the cryo-survival rate of mouse oocytes significantly declined in oocytes retrieved from mice of 40-44 weeks of age ( Table 2).…”
Section: Discussionsupporting
confidence: 57%
“…Mice are generally retired from breeding around 9 months of age [27]; however, females are still capable of ovulating and carrying offspring, albeit at a lower frequency than their younger counterparts. Previous reports have been successful in stimulating and collecting metaphase II oocytes from mice ranging from 10 to 16 months of age [7,15,[28][29][30][31]. B6D2F1 mice are considered exceptional breeders, as females regularly produce large litters (JAX® Mice; Jackson Laboratory, Bar Harbor, ME) and have a long lifespan of approximately 26 months on average (Harlan Laboratories, Indianapolis, IN).…”
Section: Animalsmentioning
confidence: 99%
“…Pregnancy success for women less than 35 years of age, transferring fresh embryos from nondonor eggs, was 47 % in 2012, while for women greater than 40 years of age, pregnancy success decreased to 15 % [2]. Advanced maternal age also affects reproductive performance in other species; aged females produce fewer oocytes in mice [6,7], horses [8], hamsters [9], and rhesus monkeys [10], and have decreased fertilization and embryo development in hamsters [9], mares [11], and mice [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many processes occur within an ageing oocyte that complicate or exclude the use of these oocytes, for example, they undergo spontaneous parthenogenetic activation, fragmentation or lysis (Petrová et al, 2004). Fragmentation is a manifestation of apoptosis (Tarin et al, 2001), which is an integral part of oocyte ageing (Yuce and Sadler, 2001). The activation of many specific molecules, for example, caspases, proteases that are responsible for dismantling of the cell, and many proapoptotic factors of the Bcl-2 gene family are necessary for the triggering of apoptosis (Adams and Cory, 1998).…”
Section: Introductionmentioning
confidence: 99%